(untitled) (Research, Society and Development, 2024)
Objective: To analyze data on COVID-19 in the Northern region of Brazil from 2020 to 2022. Methods: A retrospective cross-sectional analytical-descriptive study was conducted, using digital epidemiological and documentary data collected between 2020 and 2022. Results: The analysis of the distribution and occupancy of hospital beds, the availability and distribution of ventilators, and the distribution of medications used for COVID-19 treatment allowed the evaluation of the effectiveness of health policies implemented by state and municipal governments during the pandemic in the Northern region of Brazil. The study showed a trend of decreasing hospital bed occupancy, possibly due to increased availability, prevention measures, and mass vaccination of the population. However, it highlighted the need for a quality healthcare system with adequate resources and trained healthcare professionals to improve the response to the pandemic. Conclusion: The integrated analysis of the data on COVID-19 in the Northern region of Brazil provided a comprehensive overview of the pandemic and identified potential shortcomings in the response to it. This study highlights the need for effective and equitable health policies, resources allocation, and the adaptation of treatment strategies based on the evolution of scientific knowledge of COVID-19 and its variants.